Digging up the past - Woolley, Leonard, 1880-1960 (Baltimore : Penguin Books, 1960)
Introduction to the field of archaeology
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Excavations (Archaeology)